The Effectiveness of 30° Head-Up Intervention Patients with Moderate Head Injury Post-Craniotomy - Bilah, Natia Hasna; Ramadhan, Arieni (Jambura Nursing Journal, 2026)
Moderate head injury is a neurological condition that carries a high risk of serious complications, particularly increased intracranial pressure (ICP), thus requiring appropriate and comprehensive nursing management. A patient with moderate head injury post-craniotomy requires intensive care to prevent further neurological damage. This research aims to analyze nursing care in patients with neurological system disorders due to moderate head injury post-craniotomy through the application of a 30° head-up intervention to reduce signs of increased intracranial pressure in the ICU. The method used was a descriptive analytical method with a case study approach on Mr. O, involving data collection through observation, physical examination, interviews, documentation review, and literature review. The results of the analysis indicate that the consistent and controlled application of the 30° head-up position can help improve hemodynamics, increase the level of consciousness, and reduce signs of increased intracranial pressure. This intervention also supports improved patient comfort and prevents further complications. Therefore, the 30° head-up position can be recommended as an effective non-pharmacological intervention in the nursing care of post-craniotomy patients with moderate head injury in critical care settings.